Thermophiles and the Applications of Their Enzymes as New Biocatalysts - Blamey-Alegria, J (Elsevier Ltd, 2019)
Ecological and efficient alternatives to industrial processes have sparked interest for using microorganisms and enzymes as biocatalysts. One of the difficulties is finding candidates capable of resisting the harsh conditions in which industrial processes usually take place. Extremophiles, microorganisms naturally found in “extreme” ecological niches, produce robust enzymes for bioprocesses and product development. Thermophiles like Geobacillus, Alyciclobacillus, Anoxybacillus, Pyrococcus and Thermoccocus are some of the extremophiles containing enzymes showing special promise for biocatalysis. Glutamate dehydrogenase used in food processes, laccases and xylanases in pulp and paper processes, nitrilases and transaminases for pharmaceutical drug synthesis and lipases present in detergents, are examples of the increasing use of enzymes for biocatalytic synthesis from thermophilic microorganisms. Some of these enzymes from thermophiles have been expressed as recombinant enzymes and are already in the market. Here we will review recent discoveries of thermophilic enzymes and their current and potential applications in industry. © 2019